Influência das iniquidades socioeconômicas na ocorrência de cárie dental em adolescentes - Ortiz, Adriana Santos (2018)
The literature has shown an existence of inequalities in oral health: individuals with lower socioeconomic conditions are more likely to oral diseases, such as dental caries. However, there are not studies addressing the socioeconomic conditions and the risk of dental caries in the adolescence. In order to reduce health inequities, it is necessary to explore the causes of the disease, once it is a public health problem. The objective of this study is to evaluate the influence of socioeconomic inequities on the incidence of caries in two phases of adolescence. Data from this longitudinal study were obtained through a sample of 1,134 12-year-old children. Children were enrolled in public schools from Santa Maria, RS, Brazil in 2012. The students were re-evaluated with 14 years in 2014-2015. The outcome of this study is dental caries, evaluated through the mean decayed component of the DMF-S index in the second evaluation. Clinical variables related to dental plaque and dental crowding were also collected. Individual socioeconomic conditions were assessed through family income and maternal schooling. Data on demographic variables, psychosocial and behavioral aspects were collected through a semi-structured questionnaire. The Basic School Development Index was considered as a contextual variable. Data were analyzed using STATA 14.0 program. Unadjusted and adjusted dental caries rate ratios were estimated using multi-level Poisson regression analysis. The mean DMF-T of the sample was 1.15 (SD: 1.57) at baseline and 1.48 (SD: 1.79) at follow-up. The variables that were associated with higher mean dental caries were low IDEB, non-white skin color, lower income and frequency of dental visit, regular or poor perception of oral health and presence of dental plaque in more than 15% of the surfaces.This study showed the occurrence of socioeconomic inequities in the average dental caries of adolescents followed for 2 years a period.